GROWTH AND SURVIVAL OF THE FRESHWATER MUSSEL, ANODONTITES TRAPESIALIS (LAMARCK 1819), IN A FLOW- THROUGH SYSTEM FOR LONG-TERM HOLDING - Lima, Ricardo C. (2011)
As with other freshwater mussels, Anodontites trapesialis is an endangered and threatened species. Artificial culture has been strongly recommended in recovery plans as a strategy to bolster declining populations, as well as the reintroduction of species to sites within their historic ranges. Our project compares two methods of adult animal management: buried and suspended, focusing on growth and survival of A. trapesialis in a captive environment. Animals were fed with Chlamydomonas spp. After 120 days, weight (soft and hard body) increased by 2.1% in the suspended group and decreased by 1.4% in the buried group. Suspended animals showed higher survival rates than those that were buried. The information provided may be of particular interest to develop future conservation measures for this and other similar endangered species.